Vibrio Pathogenicity Island-1: The Master Determinant of Cholera Pathogenesis - Kumar, Ashok; Das, Bhabatosh; Kumar, Niraj (Frontiers in Cellular and Infection Microbiology, 2020)
Cholera is an acute secretory diarrhoeal disease caused by the bacterium Vibrio cholerae. The key determinants of cholera pathogenicity, cholera toxin (CT) and toxin co-regulated pilus (TCP) are the part of the genome of two horizontally acquired Mobile Genetic Elements (MGEs), CTXФ and Vibrio pathogenicity island 1 (VPI-1), respectively. Besides, V. cholerae genome harbors several others MGEs that provide antimicrobial resistance, metabolic functions and other fitness traits. VPI-1, one of the most well characterized genomic island (GI), deserved a special attention, because (i) it encodes many of the virulence factors that facilitate development of cholera (ii) it is essential for the acquisition of CTXФ and production of CT and (iii) it is crucial for colonization of V. cholerae in the host intestine. Nevertheless, VPI-1 is ubiquitously present in all the epidemic V. cholerae strains. Therefore, to understand the role of MGEs in the evolution of cholera pathogen from a natural aquatic habitat, it is important to understand the VPI-1 encoded functions, their acquisition and possible mode of dissemination. In this review, we have therefore discussed our present understanding of the different functions of VPI-1 those are associated with virulence, important for toxin production and essential for the disease development.